Economics of E-Learning in Higher Education : The Indian Case - Aggarwal, Ritika (Prabandhan: Indian Journal of Management, 2017)
Education is an important indicator of economic development and a key contributor to the Human Development Index. With the increase in global competition, countries attract human capital from across the world, and hence, education is imperative to gain competitive advantage. Also, education is a key indicator of lifetime earnings. In order to cope up with the technological changes, it is necessary for individuals to improve their skills and capabilities through education. Traditional methods of learning have become outdated and are being replaced by technology enabled education or ’e-learning’. The most important feature of e-learning is that it enables individuals to learn anytime, anywhere. Such flexibility makes learning faster, easier, and more attractive by creating a student-centred learning environment and by offering newer methods of teaching. This paper aimed to discuss the role of e-learning in the higher educational environment in this digital age, along with comparing the economic costs associated with traditional face-to-face and e-learning methods. I also reviewed several initiatives taken by the government and universities to promote e-learning in India.